Activation of organic reactions by perchlorates - Deshpande, Suvarna S.; Kumar, Anil (Advances in Organic Synthesis, 2005)
Perchlorates have been frequently employed to promote a variety of synthetic transformations under ambient conditions. For example, the LiClO4-diethyl ether solvent medium has proven to be a powerful substitute for external high pressure for Diels-Alder reactions and other organic reactions. In this chapter are discussed several such organic transformations where perchlorates have played highly significant role in promoting their rates and yields.

Stereoselectivity ratios in a simple Diels-Alder reaction in aqueous salt solutions of alcohols - Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron, 2005)
This is the first exhaustive report on the variation of stereoselectivity ratios for a simple Diels-Alder reaction between cyclopentadiene and methyl acrylate. The reaction was carried out in aqueous mixtures of methanol, ethanol, propan-1-ol and butan-1-ol in presence of LiClO4, LiCl, NaCl, KCl, CaCl2 and MgCl2. The endo sterecisomer decreases with the increase in carbon chain length of the alcohol. However, LiClO4, a salting-in agent in water becomes salting-out in aqueous mixtures of alcohols. The solvent properties, thus can be attuned by adjusting the amount of solvents and salts. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: aqueous alcohols; Diels-Alder reaction; endolexo ratios; salts

Synthesis, characterization and photo catalytic degradation of aqueous eosin over Cr containing Ti/MCM-41 and SiO2-TiO2 catalysts using visible light - Awate, S. V.; Jacob, Nalini E.; Deshpande, Suvarna S.; Gaydhankar, T. R.; Belhekar, Anagha A. (Journal of Molecular Catalysis A - Chemical, 2005)
Two series of samples were prepared namely Cr-Ti/MCM-41 and Cr/SiO2-TiO2 keeping Si/Ti mole ratio same, with different Cr loading. The physico-chemical properties of the samples were characterized by different analytical techniques such as XRD, FTIR, TEM, low temperature N-2 sorption, and UV-vis diffused reflectance spectroscopy. The impregnated TiO2 was in anatase form. The crystallite size was determined from Scherrer equation as well as by TEM. There is a difference between the shapes of nitrogen adsorption isotherms with and without Cr-loaded Ti/MCM-41 samples. The rate of nitrogen adsorption was found to increase with decrease in Cr content at lower P/P-0 for Cr-Ti/MCM-41 samples due to the blocking of the pores with Cr. All MCM-41 samples exhibited pore sizes from 24 nm to 32 nm. UV-vis diffused reflectance spectra of all Cr-loaded samples showed red shift of their absorption edges. Photo degradation of eosin dye was studied using visible light. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Cr-Ti/MCM-41; Cr/SiO2-TiO2; eosin; photo degradation; visible light

Hydrophobic effects in a simple Diels-Alder reaction in water - Sarma, D.; Pawar, S. S.; Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron Letters, 2006)
The endolexo ratio for a simple Diels-Alder reaction carried out in water has been used to argue that hydrophobic effects can dominate the geometries of the transition states. (c) 2006 Elsevier Ltd. All rights reserved.

Effect of sparger design on the flow in a bubble column: symbolic analysis of LDA data - Kulkarni, A. A.; Deshpande, Suvarna S.; Joshi, J. B.; Kumar, V. Ravi; Kulkarni, B. D. (Industrial & Engineering Chemistry Research, 2007)
This paper aims at developing a methodology that helps in the characterization of the effects of a single point and multipoint sparger on the flow patterns in a bubble column reactor. The methodology uses the simultaneously measured instantaneous velocity-time data (two orthogonal velocity components) using LDA at different measurement locations. The data sets are transformed into their equivalent description in terms of polar coordinates, viz., resultant velocity vector and angle. This information is further transformed in terms of symbolic representation in a binary number format. The covariance matrices obtained from the binary data are analyzed for their eigenvalues, and the spectrum is used for the identification of the dominant, energy containing modes in the data. In the vicinity of the sparger, the nature of covariance matrix and the eigenvalue spectrum for the single point sparger (SPS) data was significantly different from that of the multipoint sparger (MPS). In the bulk region, for both types of spargers, the nature of the eigenvalues and the number of dominant modes is seen to be different from the near sparger region. In general, more numbers of eigenvalues are required to capture the total energy in the data for a multipoint sparger when compared to a single point sparger. This suggests a higher level of complexities existing due to the intricate hydrodynamics for the multipoint sparger. The possible use of this methodology for practical purposes, e.g., identification of malfunctioning of gas-liquid sparger reactors is discussed.

Toluene alkylation with methanol to p-xylene over heteropoly acids supported by clay - Bokade, Vijay V.; Deshpande, Suvarna S.; Patil, R.; Jain, S.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{The alkylation of toluene with methanol for the selective formation of p-xylene was systematically studied. Very few studies have been reported on the use of superacids such as heteropolyacids on cheap supports, such as clay. This article deals with the use of different heteropoly acids (HPAs), viz, Dodeca-Tungstophosphoric acid [
Keywords: co-crystalline; p-xylene; toluene alkylation; ZSM-12; ZSM-5

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Transesterification of sunflower oil catalyzed by flyash-based solid catalysts - Kotwal, M. S.; Niphadkar, P. S.; Deshpande, Suvarna S.; Bokade, Vijay V.; Joshi, P. N. (Fuel, 2009)
Flyash-based base catalyst was used in the transesterification of sunflower oil with methanol to methyl esters in a heterogeneous manner. Catalyst preparation variables such as, the KNO(3) loading amount and calcination temperature were optimized. The catalysts were characterized by powder XRD. The catalyst prepared by loading of 5 wt.% KNO(3) on flyash followed by its calcination at 773 K has exhibited maximum oil conversion (87.5 wt.%). The influence of various reaction parameters such as % catalyst loading, methanol to oil molar ratio, reaction time, temperature, reusability of the catalyst on the catalytic activity was investigated. K(2)O derived from KNO(3) might be an essential component in the catalyst for its efficiency. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Flyash; heterogeneous catalyst; Methyl ester; Sunflower oil; transesterification

Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst

Influence of Al3+ insertion in the stannosilicate MFI framework on the catalytic performance in vapor phase aniline N-methylation - Niphadkar, P. S.; Joshi, P. N.; Deshpande, Suvarna S.; Bokade, Vijay V. (Applied Catalysis A-General, 2011)
Silica-based Sn-MFI, Al-MFI and Al-Sn-MFI molecular sieves were synthesized by hydrothermal crystallization of gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23 (TPA)(2)O:35H(2)O, where x ranges from 1/0 to 1/200 and y from 1/0 to 1/400. Keeping molar Si/(Al + Sn) = 50, the amount of tin and aluminum in hydrogel was varied (Sn:Al molar ratios = 1:0, 1:0.33, 1:1, 1:3, 0:1) to investigate the synergy between Lewis and Bronsted acid sites in acid catalyzed aniline N-methylation reaction. Catalyst characterization was done by Powder X-ray diffraction, DRUV-vis spectroscopy, temperature programmed ammonia desorption (TPAD) and FTIR spectroscopy. An increase in the Al3+ insertion in Sn-MFI framework resulted in the increase in the stronger acid sites. Al-Sn-MFI showed higher aniline conversion than their monometallic counterparts. A sample having B/L ratio in between 0.67 and 0.91 was found to be optimum for maximizing the NMA yield, indicating the existence synergistic properties of Al-Sn-MFI. Upon process parameter optimization, the optimum sample M50 [Si/Al = 50.2, Si/Sn = 93.8, Si/(Al + Sn) = 43.2] showed the maximum aniline conversion (67%) and NMA selectivity (81%) at reaction temperature = 220 degrees C, weight hourly space velocity (WHSV) = 3 h(-1), molar ratio (aniline to methanol) = 1:8 and TOS = 4 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-Sn-MFI; Aniline; Bronsted and Lewis acid; Methanol; N-methylaniline

Role of doping-induced photochemical and microstructural properties in the photocatalytic activity of InVO4 for splitting of water - Rakesh, K.; Khaire, S.; Bhange, Deu S.; Dhanasekaran, P.; Deshpande, Suvarna S.; Awate, S. V.; Gupta, N. M. (Journal of Materials Science, 2011)
We report in this paper on microstructural, optical and photocatalytic properties of single-phase indium orthovanadates, as a function of doping at lattice sites. The UV-visible spectra of these samples exhibited intense UV-region bands at 250 and 350 nm, besides broad absorption band in visible region (350-700 nm). The wavelength at absorption edge and the intensity of visible absorption showed considerable increase on doping of an impurity, particularly at V or O lattice sites. Also, the samples gave rise to blue-green photoluminescence emission, with overriding bands at ca. 420, 450, 460 and 485 nm, on excitation at 240-420 nm wavelengths. The intensity of these fluorescence bands varied with excitation wavelength and impurity content of a sample. In deviation with several earlier studies, only oxygen and no hydrogen were produced during photocatalytic splitting of water, in the experiments conducted under visible light (> 395 nm) and at a pH of similar to 6.5. The O-2 yield depended on the dispersed metal co-catalyst, impurity content and the addition of methanol as sacrificial reagent. On the other hand, small quantities of hydrogen and no oxygen were evolved on UV-irradiation of pure water using metal/InVO4. These results are ascribed to flat band potentials and the doping-induced inter-band donor and acceptor charge trapping states of InVO4, the presence of which is revealed by XRD, luminescence and XPS studies. Our study also confirms that the onset of absorption edge may not necessarily correspond to band-to-band energy gap of a semiconducting material. This accounts for some anomalous band gap energies reported earlier for InVO4.

Role of micro-structure and interfacial properties in the higher photocatalytic activity of TiO2-supported nanogold for methanol-assisted visible-light-induced splitting of water - Awate, S. V.; Deshpande, Suvarna S.; Rakesh, K.; Dhanasekaran, P.; Gupta, N. M. (Physical Chemistry Chemical Physics, 2011)
This paper deals with the textural, microstructural and interfacial properties of Au/TiO2 nanocomposites, in relation to their photocatalytic activity for splitting of water. TiO2 samples of two different morphologies were employed for dispersing different cocatalysts, such as: Au, Pt, Ag or Cu, for the sake of comparison. The samples were characterized using powder XRD, XPS, UV-visible, thermoluminescence, SEM, HRTEM and SAED techniques. Compared to other metal/TiO2 photocatalysts, Au/TiO2 with an optimum gold loading of 1 wt% was found to exhibit considerably higher activity for visible light induced production of H-2 from splitting water in the presence of methanol. Further, the sol-gel prepared TiO2 (s.TiO2), having spherical grains of 10-15 nm size, displayed better photoactivity than a Degussa P25 catalyst. The electron microscopy investigations on s.TiO2 revealed significant heterogeneity in grain morphology of individual TiO2 particles, exposure of the lattice planes, metal dispersion, and the interfacial metal/TiO2 contacts. The gold particles were found to be in a better dispersed state. O-2 TPD experiments revealed that the gold nanoparticles and Au/TiO2 interfaces may serve as distinct binding sites for adsorbate molecules. At the same time, our thermoluminescence measurements provide an insight into Au-induced new defect states that may facilitate the semiconductor-to-metal charge transfer transition. In conclusion, the superior photocatalytic activity of Au/TiO2 may relate to the grain morphology of TiO2, dispersion of gold particles, and the peculiar architecture of metal/oxide heterojunctions; giving rise in turn to augmented adsorption of reactant molecules and their interaction with the photo-generated e(-)/h(+) pair. The role played by methanol as a sacrificial reagent in photocatalytic splitting of water is discussed.

Synthesis, characterization and photocatalytic behavior of TiO2-SiO2 mesoporous composites in hydrogen generation from water splitting - Niphadkar, P. S.; Chitale, S. K.; Sonar, S. K.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Journal of Materials Science, 2014)
TiO2-SiO2 mesoporous composite photocatalysts with different proportions (in wt%) of TiO2 and SiO2 (TiO2-SiO2 = 20:80, 40:60, 60:40, 80:20 and 100:0) were prepared by loading TiO2 on as-synthesized Si-MCM-41 using sol-gel method. The physicochemical properties of composites were investigated by powder X-ray diffraction, N-2 adsorption-desorption measurements, transmission electron microscopy and UV-Vis diffuse reflectance spectroscopy. It is revealed that the titanium species are dispersed as TiO2 having interaction with the surface of the support. Even at high TiO2 loading, the mesostructural feature of MCM-41 was found to be intact without pore blockages. The change in morphology of TiO2 particle was observed with increase in TiO2 loading which may be due to different environment for the growth of TiO2. The photocatalytic evaluation of composites was carried out in production of hydrogen by water splitting. Among the prepared samples, mesoporous composite containing 60 % TiO2 (MTi60) has shown the best results (0.08805 mmol of H-2/h/g of TiO2) compared to other composite photocatalysts. The catalytic performance of this sample was further enhanced (similar to 8 times) after loading 1 % Pt in water splitting (0.70161 mmol of H-2/h/g of TiO2). 1 % Pt loaded on pure TiO2 (MTi100) showed hydrogen evolution of the magnitude 0.26 mmol of H-2/h/g of TiO2. TiO2-SiO2 mesoporous composite photocatalyst showed much higher activity (similar to 1.9 times) than amorphous silica-embedded titania catalyst having same composition.

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting